2016
DOI: 10.1017/pasa.2016.41
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Supermassive Black Hole Seeds

Abstract: The detection of quasars at z > 6 unveils the presence of supermassive black holes of a few billion solar masses. The rapid formation process of these extreme objects remains a fascinating and open issue. Such discovery implies that seed black holes must have formed early on, and grown via either rapid accretion or BH/galaxy mergers. In this theoretical review, we discuss in detail various BH seed formation mechanisms and the physical processes at play during their assembly. We discuss the three most popula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
124
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(129 citation statements)
references
References 252 publications
(395 reference statements)
0
124
0
Order By: Relevance
“…On the contrary, the initial growth of the other HSC quasars with sub-Eddington ratios require M seed 10 6 M seed black holes, if we assume the current growth speeds. This is even more massive than what the direct collapse model predicts (M seed ∼ 10 5−6 M ; Latif & Ferrara 2016). There is currently no plausible formation model for such an extremely heavy seed black hole.…”
Section: Implications On the Early Smbh Growthmentioning
confidence: 76%
“…On the contrary, the initial growth of the other HSC quasars with sub-Eddington ratios require M seed 10 6 M seed black holes, if we assume the current growth speeds. This is even more massive than what the direct collapse model predicts (M seed ∼ 10 5−6 M ; Latif & Ferrara 2016). There is currently no plausible formation model for such an extremely heavy seed black hole.…”
Section: Implications On the Early Smbh Growthmentioning
confidence: 76%
“…For example, "CR7" has been suggested to harbor a direct-collapse black hole, a massive seed of a supermassive black hole (e.g., Dijkstra et al 2016;Latif & Ferrara 2016). It has also been suggested that "CR7" contains PopulationIII-like stars (e.g., Pallottini et al 2015;Sobral et al 2015), though the claim is still controversial (e.g., Bowler et al 2017b).…”
Section: A Sample Of Very Luminous Laesmentioning
confidence: 99%
“…First, their very presence at such primeval cosmic times challenges models of the formation and growth of supermassive black holes (e.g., Volonteri 2010; Latif & Ferrara 2016). The current preferred models include the formation of black hole seeds from the direct collapse of massive gaseous reservoirs (e.g., Haehnelt & Rees 1993;Latif & Schleicher 2015), the collapse of Population III stars (e.g., Bond et al 1984;Alvarez et al 2009;Valiante et al 2016), the co-action of dynamical processes, gas collapse and star formation (e.g., Devecchi & Volonteri 2009), or the rapid growth of stellar-mass seeds via episodes of super-Eddington, radiatively inefficient accretion (e.g., Alexander & Natarajan 2014;Madau et al 2014;Pacucci et al 2015;Lupi et al 2016;Pezzulli et al 2016;Volonteri et al 2016;Begelman & Volonteri 2017 , assuming accretion at the Eddington limit and an efficiency of 10%; Volonteri & Rees 2005).…”
Section: Introductionmentioning
confidence: 99%